Interactions between Nb-Si based ultrahigh temperature alloy and yttria matrix mould shells. (15th February 2017) - Wang, Yin; Guo, Xiping; Qiao, Yanqiang
Abstract: To find the best mould shells for investment casting of Nb-Si based ultrahigh temperature alloy, Y2 O3 mould shells with zirconia face coat and yttria face coats doped without and with CaO + ZrO2, MgO + ZrO2, La2 O3  + ZrO2 and CeO2  + ZrO2 were prepared and their interactions with the melt of the alloy at 1850 °C for 30 min were investigated. The results show that the interfaces between the alloy and the mould shells with yttria face coats doped with CaO + ZrO2, MgO + ZrO2 and La2 O3  + ZrO2 during re-melting process all comprise two types of reaction layers, which are mainly composed of HfO2  + Y2 O3 and TiO + HfO2 . The interface between the alloy and the mould shell with yttria face coats doped with CeO2  + ZrO2 is also composed of two types of reaction layers, which consist of HfO2  + Y2 O3 and cubic HfO2 respectively. A single reaction layer consisting of HfO2  + Y2 O3 constitutes the interface between the alloy and the pure yttria mould shell, and the interface between the alloy and the mould shell with zirconia face coat is also composed of a single reaction layer but consisting of cubic HfO2 . Both pure yttria and yttria doped with La2 O3  + ZrO2 mould shells are more suitable for the investment casting of the alloy. Graphical abstract: Highlights: Y2 O3 matrix mould shells with yttria face coats doped with different oxides were prepared via lost wax process. Discontinuous Ti solid solution layer existed along the boundary of alloys re-melted in Y2 O3 mould shells doped with oxides. Two reaction layers could be found between the alloys and Y2 O3 mould shells doped with oxides. Mould shells of pure yttria and yttria doped with La2 O3  + ZrO2 are fit for the casting of Nb-Si based alloys.